KLASIFIKASI FASE TUMBUH PADI DAERAH INDRAMAYU - Tandiono, Alfin (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Klasifikasi Fase Tumbuh Padi Daerah Indramayu is a research to classify paddy grow phase in Indramayu using MODIS image. The Methode we used to classify in this research is using Principle Component Analysis (PCA), Norm Vector and F Distribution. Classification Process is start from using the Modified PCA Method for dimension reduction. This PCA is already modified by using the Scalling or Centering in purpose to normalized the data. After the dimension of data already reduced, the next step is measuring the Norm with point 0,0 to search the maximum range. The maximum Norm will be centroid of a new cluster. Next, measure all of range from every observation with the centroid using Squared Mahalanobis Distance. After that, distributed them using the F Distribution. The last step is make the range of cluster that used for classify the data training. Data testing will used half of the first subset data and using the MODIS image. This research will give an output Distribution Map. The evaluation is still not reach the good one because some of factor that make the result bad. The evaluation is still never through out 50%. Key words : F Distribution, Norm Vector, Principle Component Analysis, Range Data Class, Squared Mahalanobis Distance